Overlapping Authority Between BPN and Ministry of Energy and Resources in Issuing Certificates of Right of use and Mining Business Permits - Ningrum, Nurohmah Rosia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The overlapping authority between the National Land Agency (BPN) and the Ministry of Energy and Mineral Resources (ESDM) remains a persistent issue in Indonesia’s legal system, particularly regarding the issuance of land use certificates (SHP) and mining business permits (IUP). The inconsistency between the Basic Agrarian Law (UUPA) of 1960 and Law No. 4/2009 jo. Law No. 3/2020 on Mineral and Coal Mining (Minerba Law) has resulted in legal uncertainty and conflicts between land and mining rights. This study employs a normative juridical method through statutory, conceptual, and case approaches, with Bandung High Court Decision No. 116/PDT/2020/PT BDG as its primary source. The findings reveal that a mining business permit cannot nullify existing land rights, and every IUP holder must first settle land ownership status before conducting mining operations. The hierarchy of laws places the UUPA as the superior legal norm, while the Minerba Law serves as a sectoral regulation subject to the principle of lex superior derogat legi inferiori.